Dynamic interaction between economic growth and energy in Malaysia - Tan, Chiang Ching (Universiti Malaysia Sarawak (UNIMAS), 2015)
This thesis attempts to investigate the causal relationship between economic growth (or GDP) and disaggregate energies (energy supply and consumption) in Malaysia by applying the time-series techniques. The major findings for energy supply extract from this thesis are as follows: (1) Long run causality was detected from oil and coal supply to GDP. (2) Short run unidirectional causality exists running from GDP to petroleum and gas supply. (3) The results of the variance decompositions suggest that coal and oil supply are relatively more important on GDP if compare to other energy supplies. As for energy consumption, the major findings are: (i) Causality relationship from gas and CO2 to GDP exists in both the long and short run. (ii) Short run unidirectional causality exists running from electricity to CO2. (iii) The results of the variance decompositions suggest that oil and electricity consumption are relatively more important on GDP beyond the sample.